A cross-sectional study to find out the prevalence of Cardiac autonomic neuropathy (CAN) in Diabetes Mellitus cases in a tertiary care hospital - Dr Prodeep Kumar Padhy, Dr (Prof) Rajendra Kumar*, Dr. Neetika (Innovative Journal of Medical and Health Sciences, 2020)
Objective: To find out the prevalence of Cardiac autonomic neuropathy (CAN) in Diabetes Mellitus cases in a tertiary care hospital. Methods: This was a cross-sectional study conducted in a tertiary care hospital. The study was approved by the Ethical Committee of the Institute and consent was taken from each participants before enrolling in the study. A total of 128 patients with diabetes mellitus for more than 5 years were included in the study. The classification of CAN was done as per Ewings and Clarke criteria. Results: The prevalence of CAN was found to be 47.7% (61/128). Definite CAN was among majority of patients (67.2%) followed by early (29.5%) and advance (3.3%). Valsalva, E-I and 30:15 ratio was abnormal among 43%, 71.9% and 64.8% patients respectively. The prevalence of CAN was higher among whom Valsalva was abnormal (52.7%) than borderline (45.5%) and normal (38.9%). However, the prevalence of CAN was higher among whom E-I was borderline (52.4%) than abnormal (50%) and normal (26.7%). There was no significant (p>0.05) association of prevalence of CAN with Ewing’s criteria variables. Conclusion: Cardiac Autonomic Neuropathy thus is most frequently asymptomatic problem which can be identified by simple bed side tests. Early identification of Cardiac Autonomic neuropathy helps in effective prevention of cardiovascular disease related morbidity and mortality. Key words: Diabetes Mellitus–Cardiac Autonomic Neuropathy–Prevalence